2012
DOI: 10.1007/s12177-012-9096-8
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases (MMP-2 and MMP-9) activity in corneal ulcer and ocular surface disorders determined by gelatin zymography

Abstract: The purpose of this paper is to determine the active form of matrix metalloproteinases (MMP-2 and MMP-9) in corneal ulcer and ocular surface disorder patients. A total of 35 patients of corneal ulcer, 20 patients of ocular surface disorders and 10 control subjects were included in this study and estimation of active form of MMP-2 and MMP-9 was done by gelatin zymography. Tear samples were collected by capillary tube method. Both pro-and active forms of MMP-9 were detected in 24 out of 35 patients with corneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Gelatin zymography is a method used for easy detection of latent and active MMPs. Because the active forms of MMPs are water-soluble enzymes, it is difficult to detect by immunohistochemical or molecular biological method ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatin zymography is a method used for easy detection of latent and active MMPs. Because the active forms of MMPs are water-soluble enzymes, it is difficult to detect by immunohistochemical or molecular biological method ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al ( 68 ) demonstrated that the active forms of MMP-9 are present in tears of severe ulcerative and ocular surface disorder patients with no detection in the control group. Also, an injury without bacterial infection resulted in an increase in both MMP-2 and−9 and a slight but significant downregulation of TIMP-1 in mouse corneal ulcer ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…67 The role of MMPs in corneal melt, intuitive if one considers the predominance of collagen in the structure of corneal stroma, is well documented. 7,8,57,63,76,87 Specifically for NICM, the study of three cases of diclofenac-induced corneal melt with perforation revealed enhanced expression of MMPs 1 and 9 within corneal epithelial cells, stromal keratocytes, and at the level of the Descemet membrane. 34 Their uniform distribution pattern of expression was not consistent with the localization expected of a repair response.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…In the end, destining solution (10% acetic acid and 30% methanol) have been used in removing color. After gel drying, it was analyzed by Image J …”
Section: Methodsmentioning
confidence: 99%